New developments in psychological choice modeling - Soete, Geert de; Feger, Hubert; Klauer, Karl C. (Advances in psychology (Amsterdam, Netherlands) ;, 1989)
A selection of 15 papers on choice modeling are presented in this volume. These papers result from research in the social and behavioral sciences and in economics. The models, some deterministic, some probabilistic, represent recent developments in the tradition of Thurstone's Law of Comparative Judgement, Coombs' unfolding theory and multidimensional scaling. The theoretical contributions and several applications to voting behaviour, consumer research and preference rankings show the important progress made in psychological choice modeling during the last few years.